2000
DOI: 10.1023/a:1008934024440
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The kinetics of hydroxyapatite (HAp) formation by direct hydrolysis of alpha-tricalcium phosphate (alpha-TCP) [alpha-Ca(3)(PO(4))(2)] have been investigated. Transformation kinetics were examined for reactions at 37 degrees C, 45 degrees C and 56 degrees C by isothermal calorimetric analysis. Setting times and morphologies of the resultant HAp were found to be strongly dependent on reaction temperature. XRD analysis accompanied by FTIR confirmed that phase pure calcium-deficient hydroxyapatite (CDHAp) [Ca(10-x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 10 publications
4
40
0
1
Order By: Relevance
“…13 shows SE-micrographs of the sample G/S (75:25 wt.%) after immersion in 1.5 SBF for 3 days. Consistent with the results reported by Durucan and Brown [69] the CO 3 HA formed in flake-like morphology with smaller crystalline size. EDS of the sample gave Ca/P of 1.82.…”
Section: Ftir Of the Prepared Hybrids After Immersion In 15 Sbf For supporting
confidence: 91%
“…13 shows SE-micrographs of the sample G/S (75:25 wt.%) after immersion in 1.5 SBF for 3 days. Consistent with the results reported by Durucan and Brown [69] the CO 3 HA formed in flake-like morphology with smaller crystalline size. EDS of the sample gave Ca/P of 1.82.…”
Section: Ftir Of the Prepared Hybrids After Immersion In 15 Sbf For supporting
confidence: 91%
“…In the absence of humidity, both polymorphs of TCP are stable at room temperature; however, a density functional study [295] has shown that the stability of the β-TCP crystal lattice exceeds that of α-TCP. Therefore, of the two, α-TCP is more reactive in aqueous systems, has a higher specific energy, and can be hydrolysed in aqueous solutions to CDHAp [296,297]. Although α-TCP never occurs in biological calcifications, it is used as a component of CaP cements [256,260,261,262,263,264].…”
Section: Individual Calcium Phosphate Phases and Their Propertiesmentioning
confidence: 99%
“…The details on α-TCP hydrolysis are also available. The results indicated that setting of α-TCP was initially controlled by surface dissolution; therefore, it depended on the surface area of the reactants [213,214,215,216]. Hydrolysis of DCPD to CDHA was studied as well [217].…”
Section: General Information and Knowledgementioning
confidence: 99%